PERENCANAAN SISTEM DRAINASE KALI KENDAL - Sukma Adji Nugrahedi; Adi Saputra; Suripin Suripin; priyo Nugroho P. (Jurnal Karya Teknik Sipil, 2014)
Kendal river is always overtopped during rainy day, certainly in central city and densely populated area. The flood duration around 4-8 hours with 40-60 cm depth caused the secondary channel can’t flow into the primary channel. The problem of flooding caused by the capacity of Kendal River is decreasing. Base on that condition, this final project was aimed to redesign Kendal River system based on capacity and functionality. The first step on redesign drainage system is hidrology analysis for determining a flood discharge, analysis hidrolic analysis by HEC-RAS software to evaluate the capacity exsisting channel. The conclution of the evaluation result is the maximum channel capacity could be increased to 10 years discharge flood only (34,94 m3/s). Increase the capasity of the trapezium channel by enlarge a basis channel along 10 m at Kendal River (11,750 m), include the revetment construction (2,300 m) on P.5+050 – P.10, P.11 - P.12, P.13+050 - P.15, P.44+050 - P.45+050, P.65 - P.80. Anchored wall construction decided as a retaining wall for a rectangular channel type (2,050 m) at P.24 - P.4+050. And then, for accomodate 25 years flood discharge (45,43 m3/s) need 7 ha retention pond. Total cost is Rp. 63,847,420,000,00 for 10 years discharge desain.